2019
DOI: 10.1186/s12960-019-0350-z
|View full text |Cite
|
Sign up to set email alerts
|

“Practice so that the skill does not disappear”: mixed methods evaluation of simulator-based learning for midwives in Uganda

Abstract: Background Postpartum hemorrhage and neonatal asphyxia are leading causes of maternal and neonatal mortality, respectively, that occur relatively rarely in low-volume health facilities in sub-Saharan Africa. Rare occurrence of cases may limit the readiness and skills that individual birth attendants have to address complications. Evidence suggests that simulator-based training and practice sessions can help birth attendants maintain these life-saving skills; one approach is called “low-dose, high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…The mean number of practice sessions per provider was calculated from providers’ recording of their practice sessions on logs. This is reported elsewhere [22].…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…The mean number of practice sessions per provider was calculated from providers’ recording of their practice sessions on logs. This is reported elsewhere [22].…”
Section: Methodssupporting
confidence: 81%
“…Composite scores of care to the mother and newborn were significantly higher at endline for the intervention groups with PAL compared to the control. All facilities in the intervention groups had a Clinical Mentor to facilitate deliberate practice—the PAL approach—resulting in more skills practice than reported in the control group [22].…”
Section: Discussionmentioning
confidence: 99%
“…Intrapartum stillbirths decreased by 34% and early neonatal deaths decreased by 62% from baseline to endline, and remained reduced for 6–9 months post intervention 18 . Interviews with facility staff and district trainers suggested that facility staff who practiced more were motivated by a desire to maintain skills and be prepared for emergencies, external recognition, and establishing a set schedule for practice 19 .…”
Section: Discussionmentioning
confidence: 99%
“…It may save precious maternal and neonatal lives by improving the expertise and skills as well as preparing them for such events. Purpose is to establish the facilitators and obstacles in "low-dose, high-frequency" (LDHF) practice [29] (Figure 6).…”
Section: Simulator-based Trainingmentioning
confidence: 99%